2014
DOI: 10.1111/afe.12068
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneity and composition of agricultural landscapes influence native and exotic coccinellids in alfalfa fields

Abstract: 1 The current trend toward simplification of agricultural landscapes, as well as the associated loss of perennial cover types, can decrease landscape heterogeneity and also natural enemy abundance and diversity, favouring exotic species. 2 We evaluated the effects of agricultural landscape composition and heterogeneity at two different spatial scales (radii of 250 and 1000 m), on the diversity and abundance of native and exotic coccinellids, associated with alfalfa fields located in two regions of Central Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
(78 reference statements)
2
21
1
Order By: Relevance
“…Nevertheless, the fact that H. axyridis represents 20.2% of all ladybirds on pine in north-western Switzerland prompts us to suggest further studies in this habitat. Furthermore, various studies, mostly from the Americas, showed that it can also become very abundant on annual crops, such as alfalfa fields in Chile [ 9 , 27 ] potato fields [ 28 ] or across agricultural landscapes [ 6 , 8 , 13 ] in USA. Thus, their impact on both aphids and aphidophagous insects in such habitats should also be investigated in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the fact that H. axyridis represents 20.2% of all ladybirds on pine in north-western Switzerland prompts us to suggest further studies in this habitat. Furthermore, various studies, mostly from the Americas, showed that it can also become very abundant on annual crops, such as alfalfa fields in Chile [ 9 , 27 ] potato fields [ 28 ] or across agricultural landscapes [ 6 , 8 , 13 ] in USA. Thus, their impact on both aphids and aphidophagous insects in such habitats should also be investigated in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…However, this scenario is not the case further afield. In North America, H. axyridis is abundant on cotton (Conway and Kring 2010), maize (Musser andShelton 2003, Hesler andKieckhefer 2008), potato (Alyokhin and Sewell 2004), soybean (Hesler 2014) and wheat (Nault and Kennedy 2003) while in Chile it occurs nearly exclusively on alfalfa (Grez et al 2014(Grez et al , 2016. The variation in host plant preference globally may be a consequence of the global genetic diversification of the populations (Lombaert et al 2010), variations in flight capacity (Lombaert et al 2014), and opportunistic preferences for anthropogenic habitats (Sloggett 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Harmonia axyridis was sampled in spring (September–October) and autumn (March–April) from 2010 to 2014, with the exception of 2013, in eight habitats (land cover types) present near Santiago, the region of our first record. The dominant land cover types, which have been shown to be favourable habitats for coccinellids (Grez et al ., , ) in the landscape were sampled: four agricultural crops: alfalfa, annual crops (wheat), vineyards and orchards (plums and walnuts); three semi‐natural habitats (anthropogenic unmanaged habitats): blackberry strips, eucalyptus woodlands, tree hedgerows; and a natural habitat: sclerophyllous matorral. Each land cover type was replicated five to 13 times across the landscape, with replicates separated by at least 400 m. In each season, coccinellids were sampled for 2 weeks by placing five unbaited yellow sticky card traps (15 × 25 cm, two‐faced) towards the centre of each patch, 80 cm above ground, and separated by at least 10 m. The sampling height was uniform in different habitats based on previous observations in arboreal vegetation in the same region, in which traps located at 0.8 m captured ladybirds while those at 9 m did not capture any (unpublished data).…”
Section: Methodsmentioning
confidence: 99%